2014
DOI: 10.5539/gjhs.v6n3p241
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effect of Transactional Model-Based Teaching and Ordinary Education Curriculum- based Teaching Programs on Stress Management among Teachers

Abstract: Background and Objectives:Regarding the effect of teachers’ stress on teaching and learning processes, the researchers decided to provide a stress management program based on Transactional Model to solve this teachers’ problems. Thus, this study is going to investigate the effect of Transactional Model- based Teaching and the Ordinary Education Curriculum- based Teaching programs on Yazd teachers.Methods:The study was a semi- experimental one. The sample population (200 people) was selected using categorized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
2
6
1
Order By: Relevance
“…In this study, SPSS software (version 19) was used to analyze the data. Pearson correlation coefficient, independent t-test, one-way ANOVA and linear regression were used to evaluate the relationship between variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, SPSS software (version 19) was used to analyze the data. Pearson correlation coefficient, independent t-test, one-way ANOVA and linear regression were used to evaluate the relationship between variables.…”
Section: Discussionmentioning
confidence: 99%
“…The second section included the questions about coping strategies that was used from the Lazarus and Folkman model of stress and coping. Therefore, initial scales were designed by studying the related tools about coping of mothers with their child's disease [9,[17][18][19]. Then, the validity and reliability of the questionnaire was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there have been only a few studies examining the effectiveness of interventions based on the Lazarus and Folkman’s model. The results of a study showed that both patterns reduced stress among teachers, where the transactional model of stress and adaptation was more effective compared to the usual education program [ 15 ]. Another study indicated that multifaceted treatment of Lazarus had a significant effect on the general health.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been only a few studies examining the effectiveness of interventions based on the Lazarus and Folkman's model. The results of a study showed that both patterns reduced stress among teachers, where the transactional model of stress and adaptation was more effective compared to the usual education program (15). Another study indicated that multifaceted treatment of Lazarus had a signi cant effect on the general health.…”
Section: Introductionmentioning
confidence: 99%